RHO KINASE BLOCKADE ALLEVIATE BLOOD PRESSURE ELEVATION AND INHIBIT VASCULAR REMODELING IN APATINIB-INDUCED HYPERTENSION–TO BE CONFERMED. (June 2022) - Li, Caie; Wang, Qiongying; Ma, Liping; Wang, Wenjuan; Yu, Jing
Abstract : Objective: Hypertension and kidney injury are two of the major adverse effects of the targeted anti-tumor drug apatinib, it was suspected that hypertension may be the result of renal dysfunction in some of the previous studies. The present study was designed to explore the different responses of blood pressure and kidney in the apatinib-induced hypertensive rat model. Design and method: 30 Wistar-Kyoto rat were randomly divided into 3 groups, each group was administered with 2 mL 0.9% saline, 30 mg/d of apatinib or 15 mg/d of apatinib by oral gavage for 2 weeks. Blood pressure was monitored at the baseline and during the treatment. Level of creatinine, urea nitrogen, sodium, albumin and protein in blood and urine were tested both at baseline and at the end of the treatment. Urinary sodium excretion and glomerular filtration rate was calculated. Specific mRNA and proteins were detected at the end of the treatment. Results: Average mean blood pressure (MBP) in the high dose apatinib group was 105 mmHg at the 9th day and 113 mmHg at the 15th day, average MBP in the low dose apatinib was 98 mmHg at the 9th day and 108 mmHg at the 15th day. MBP were significantly high in apatinib group, no matter in the high dose or low dose (p < 0.01). Compared with the control group, the level of endothelin 1(ET-1) and college-1 were significantly high in both apatinib group (p < 0.01). There was no significant differences of urinary sodium excretion, glomerular filtration rate and microalbuminuria between the control group and the low dose apatinib group, while that in the high dose apatinib group were significantly high (p < 0.01). Conclusions: There are differences in the response to different doses of apatinib between blood pressure and kidney, blood pressure was elevated even at a relevantly lower dose of apatinib, which was accompanied with the elevation of ET-1 level and vascular emodelling, while the kidney injury occurred only at higher dose of apatinib. The hypertension induced by apatinib was independent with kidney injury caused by the drug, not the consequence of it.